2020
DOI: 10.3390/ijms21031142
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Blood Biomarkers for Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a devastating illness whose biomedical basis is now beginning to be elucidated. We reported previously that, after recovery from frozen storage, lymphocytes (peripheral blood mononuclear cells, PBMCs) from ME/CFS patients die faster in culture medium than those from healthy controls. We also found that lymphoblastoid cell lines (lymphoblasts) derived from these PBMCs exhibit multiple abnormalities in mitochondrial respiratory function and signallin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 49 publications
0
39
0
3
Order By: Relevance
“…An increase in proton leak would usually correspond to decreased mitochondrial efficiency, as observed in two other studies by Missailidis et al [12,22,23,36]. Missailidis et al showed that respiratory function parameters can be part of an effective method to distinguish between ME/CFS/SEID and HC participant cells, however these findings require further validation in a larger cohort [23]. It is difficult to make reliable conclusions based on the glycolytic activity and respiratory function described in these featured studies, further research is required.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…An increase in proton leak would usually correspond to decreased mitochondrial efficiency, as observed in two other studies by Missailidis et al [12,22,23,36]. Missailidis et al showed that respiratory function parameters can be part of an effective method to distinguish between ME/CFS/SEID and HC participant cells, however these findings require further validation in a larger cohort [23]. It is difficult to make reliable conclusions based on the glycolytic activity and respiratory function described in these featured studies, further research is required.…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, two papers reported decreased proton leak with decreased mitochondrial efficiency parameters in ME/CFS/SEID patients [12,19]. An increase in proton leak would usually correspond to decreased mitochondrial efficiency, as observed in two other studies by Missailidis et al [12,22,23,36]. Missailidis et al showed that respiratory function parameters can be part of an effective method to distinguish between ME/CFS/SEID and HC participant cells, however these findings require further validation in a larger cohort [23].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations